Convergence Results on the Boundary Conditions for 2D Large-Scale Primitive Equations in Oceanic Dynamics. (18th July 2020) - Li, Yuanfei
Abstract : In this paper, the initial boundary value problem for the two-dimensional large-scale primitive equations of large-scale oceanic motion in geophysics is considered, which are fundamental models for weather prediction. By establishing rigorous a priori bounds with coefficients and deriving some useful inequalities, the convergence result for the boundary conditions is obtained.